Basic needs in online learning during covid-19 : a Malaysian students’ survey - Zambri Harun,; Firdaus Mohamad Hamzah,; Zulkhairi Zainol Abidin,; Wan Fathul Hakim Wan Zamri,; Hashimah Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The COVID-19 pandemic has ravaged many nations economically and socially. This survey study involved Malaysian students in the tertiary level on their perspectives of online learning - their only possible method of learning throughout almost two-year of the lockdown. The online survey involved 1410 students in science, technology and engineering programmes throughout public and private universities in Malaysia. This study involves perceptions such as an increase in the level of difficulties in technical courses and compared with humanities course and students’ thoughts had they been in different scenarios. Some statistical tests on correlations of important parameters are performed. Despite a well-perceived success in online education, in a contrasting student perspective, there were many challenges faced by students from access to decent device and internet connection to a more mental-related issue such as their study environments. It is possible that the basic expectations in Maslow's hierarchy of needs model in online education are not met. More than 80% of students reported that technical-based courses such as computer programming or material science were harderin online learning. Again, more than 80% of students reported that it would be easier to understand the subject if they had a peer around. To stay current, universities will need to find ways to offer online education with a local blend to their current and prospective students.